Vibration‐based piezoelectric, electromagnetic, and hybrid energy harvesters for microsystems applications: A contributed review. (3rd July 2020) - Iqbal, Muhammad; Nauman, Malik Muhammad; Khan, Farid Ullah; Abas, Pg Emeroylariffion; Cheok, Quentin; Iqbal, Asif; Aissa, Brahim
Summary: Wireless sensor nodes (WSNs) and embedded microsystems have recently gained tremendous traction from researchers due to their vast sensing and monitoring applications in various fields including healthcare, academic, finance, environment, military, agriculture, retail, and consumer electronics. An essential requirement for the sustainable operation of WSN is the presence of an uninterrupted power supply; which is currently obtained from electrochemical batteries that suffer from limited life cycles and are associated with serious environmental hazards. An alternative to replacing batteries of WSNs; either the direct replacement or to facilitate battery regular recharging, is by looking into energy harvesting for its sustainable drive. Energy harvesting is a technique by which ambient energy can be converted into useful electricity, particularly for low‐power WSNs and consumer electronics. In particular, vibration‐based energy harvesting has been a key focus area, due to the abundant availability of vibration‐based energy sources that can be easily harvested. In vibration‐based energy harvesters (VEHs), different optimization techniques and design considerations are taken in order to broaden the operation frequency range through multi‐resonant states, increase multi‐degree‐of‐freedom, provide nonlinear characteristics, and implement the hybrid conversion. This comprehensive review summarizes recent developments in VEHs with a focus on piezoelectric, electromagnetic, and hybrid piezoelectric‐electromagnetic energy harvesters. Various vibration and motion‐induced energy harvesting prototypes have been reviewed and discussed in detail with respect to device architecture, conversion mechanism, performance parameters, and implementation. Overall sizes of most of the reported piezoelectric energy harvesters are in the millimeter to centimeter scales, with resonant frequencies in the range of 2‐13 900 Hz. Maximum energy conversion for electromagnetic energy harvesters can potentially reach up to 778.01 μW/cm 3 . The power produced by the reported hybrid energy harvesters (HEHs) is in the range of 35.43‐4900 μW. Due to the combined piezoelectric‐electromagnetic energy conversion in HEHs, these systems are capable of producing the highest power densities.